Growth and characterization of GaAs1and#x2212;xSbx nanowires - Yuan, X; Tan, H; Parkinson, P; Wong-Leung, J; Breuer, S; Gao, Q; Jagadish, C (2012)
We report the structural and optical characterization of GaAs 1-xSbx nanowires (NWs) grown on GaAs (111)B substrates using metalorganic chemical vapour deposition (MOCVD). The NWs are perpendicular to the substrate with almost defect-free zinc blende (ZB) structure. Micro-photoluminescence results demonstrate high emission efficiency at around 1.3 μm from the NWs. © 2012 IEEE.